A Comment on "Kin Networks and Institutional Development" - Jean Degroot; Paula E. Gobbi; Alejandra Ramos; Xinyu Wei (Institute for Replication (I4R), 2024)
Schulz (2022) shows how weak kin networks contributed to the rise of participatory institutions and how the medieval Catholic Church marriage regulations prohibitions contributed to the process by destroying European clan-based kin networks. Three pieces of evidence construct the argument. First, a cross-country level analysis shows that countries with cousin-term differentiation score between 2.83 and 7.66 units less in modern democracy than non-differentiating countries. The point estimates are statistically significant at the 5% level using Conley SEs either at the genetic distance or geographical distance level. Second, a historical analysis shows that one additional century of exposure to the Western Church increased the probability of a city being a commune by 12.2 and is statistically significant at the 1% level using Conley SEs with distance cutoffs of 500km or 2,500 km. Third, a 20th century analysis of voter turnover and kin network within European countries shows that doubling cousin marriage rate decreases the probability to vote by about 1.8 percentage points. Following an epidemiological approach that links the kin-network of migrant mothers country of origin to the second-generation migrant's political participation in Europe, Schulz (2022) shows that cousin-term differentiation in the country of origin of the second-generation migrant mother reduces the probability of voting. The above results are all computationally reproducible. We only identify two minor coding errors: the SE in reported in Table 3 correspond to SE clustered at the city level rather than Conley SE, and the sample size in Table 5 is incorrect. None of the errors affects the point estimates or their statistical significance. We also provide the missing code for the two figures in the paper. For the historical analysis, we conduct a robustness check on alternative sample of cities. The magnitude of the coefficients exhibits a very small variation and statistical significance of the results remains unchanged.
Keywords: 330